Conceptualising personal and historical nostalgia as travel motives - Asenjo, Carolina; Quintal, Vanessa; Marchegiani, Chris (School of Marketing, Curtin Business School, 2009)
This conceptual paper reviews the literature that recognises the growing importance of nostalgia within the consumer goods markets and the existence of several types of nostalgia. It proposes a research model which examines the significance of nostalgic emotions within a leisure travel context. Specifically, it seeks to examine personal and historical nostalgia's relevance as travel motives that influence travel attitudes and travel intentions toward a tourist destination. Perceived travel risk is also investigated as a potential moderator between travel attitudes and travel intentions. Relevant theories are reviewed to try explain the various relationships and the paper concludes with a set of hypotheses.